Revisiting George Orwell's Animal Farm, Yasar Kemal's The Sultan of the Elephants and the Red-Bearded Lame Ant within the Context of Socialist Realism - Ayyildiz, Nilay Erdem (Knowledge Hub Publ Co Ltd, 2021)
English author George Orwell (1903-1950)'s novella Animal Farm (1945) is an allegorical portrayal of the difficulty of creating classless societies because of power-hungry leaders. Likewise, Yaw Kemal (1923-2015)'s children's novel entitled The Sultan of the Elephants and the Red-Bearded Lame Ant (1975) depicts elephants and ants in an anthropomorphic portrayal of totalitarianism. This study intends to disentangle two authors' socialist realist depiction thorough these works from distinct literatures. Therefore, the study aims at comparing and contrasting Orwell's and Kemal's selected works to indicate how socialist realism functions through the genre, characters and content in the works. The study applies for the tenets of socialist realist literature stated by Maxim Gorky (1868-1963), who is among the leading founders of socialist realist literary theory, to enrich the close reading of the selected works. The analysis indicates that although they appeared in different countries and years, they bear parallelism in terms of genre, characters and content within the context of socialist realism. However, while Animal Farm warns against the betrayal of the revolution through his suspicious approach to the realisation of a socialist society, The Sultan of the Elephants and the Red-Bearded Lame Ant creates hope out of despair for a socialist society.
Keywords: Yasar Kemal; The Sultan of the Elephants and the Red-Bearded Lame; Ant; George Orwell; Animal Farm; socialist realism